Self-Regulation and Language Students’ Learning Experience - Salamanca González, Fredy Orlando (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The aim of this reflective article is to display the relationship between B.A. students learning experience and self-regulation metacognitive skills. It is a demanding task for a teacher to assess their apprentices in terms of their individual academic needs and capabilities. Self-regulation metacognitive skills can empower students with the tools to recognize themselves as learners with different expectations and aptitudes. The challenge for current classrooms is to work on making students aware and responsible for their own learning. Commitment and discipline are key aspects of becoming a self-regulated learner.